Mitochondria are selectively eliminated from eukaryotic cells after blockade of caspases during apoptosis. - Xue, L; Fletcher, G; Tolkovsky, A (2001)
Pan caspase inhibitors are potentially powerful cell-protective agents that block apoptosis in response to a wide variety of insults that cause tissue degeneration. In many conditions, however, the blockade of apoptosis by caspase inhibitors does not permit long-term cell survival, but the reasons are not entirely clear. Here we show that the blockade of apoptosis by Boc.Aspartyl(O-methyl)CH2F can result in the highly selective elimination of the entire cohort of mitochondria, including mitochondrial DNA, from both neurons and HeLa cells, irrespective of the stimulus used to trigger apoptosis. In cells that lose their mitochondria, the nuclear DNA, Golgi apparatus, endoplasmic reticulum, centrioles, and plasma membrane remain undamaged. The capacity to remove mitochondria is both specific and regulated since mitochondrial loss in neurons is completely prevented by the expression of the antiapoptotic protein Bcl-2 and partially suppressed by the autolysosomal inhibitor bafilomycin. Cells without mitochondria are more tolerant to an anaerobic environment but are essentially irreversibly committed to death. Prevention of mitochondrial loss may be crucial for the long-term regeneration of tissues emerging from an apoptotic episode in which death was prevented by caspase blockade.